Religion und Politik im Mittelalter: Deutschland und England im Vergleich : Germany and England by comparison ; [papers presented at the conference of the Prince Albert Society held at Coburg in 2010] = Religion and politics in the Middle Ages - Körntgen, Ludger; Waßenhoven, Dominik (Prinz-Albert-Studien, 2013)
Religion and politics in the reign of Charlemagne / Janet L. Nelson -- Bischöfe als Königsmacher? : Selbstverständnis und Anspruch des Episkopats bei Herrscherwechseln im 10. und frühen 11. Jahrhundert / Dominik Wassenhoven -- Individual and collective sinning in tenth- and eleventh-century England : penance, piety and the law / Catherine Cubitt -- A view from afar : English perspectives on religion and politics in the investiture conflict / Stuart Airlie -- Der Investiturstreit und das Verhaltnis von Religion und Politik im Frühmittelalter / Ludger Körntgen -- Karl der Grosse : ein "politischer Heiliger" im 12. Jahrhundert? / Knut Görich -- Bishops and Kings in England, c.1066-c.1215 / Björn Weiler -- The English monarchy and the promotion of religion in the fourteenth century / W. Mark Ormrod -- Religion und Politik im spätmittelalterlichen deutschen Reich / Amalie Fössel